Pemberian Relaksasi Dan Stimulasi Humor Terhadap Penurunan Stres Pada Anak - Yuliani, Naning (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
This research aims to reduce stress levels in children (puberty age) by providing relaxation and humor stimulation. The 12 research subjects were children aged 11 to 15 years with moderate stress categories and a sense of humor at medium and high levels. The subjects were divided into 3 groups, namely: 1) relaxation only, 2) humor stimulation only, and 3) relaxation and humor stimulation. To measure stress, a stress scale is used based on aspects of distress proposed by Patel (1996). To measure the control variable, namely sense of humor, the Multidimensional Sense of Humor Scale (MSHS) proposed by Thorson & Powell (1993) was used which has been modified by researchers based on forms of sense of humor. The results show that relaxation combined with humor stimulation can further reduce stress levels when compared to relaxation given without humor stimulation. On the other hand, humor stimulation is less effective in reducing stress, which can be caused because stress itself comes from many factors, namely from within the individual himself (internal source) as well as from outside the individual (external source).